Landslide susceptibility assessment for cameron highlands using analytical hierarchy process - Hanafiah M.I.M.; Solemon B.; Omar R.; Roslan R.; Wahab W.A.; Baharuddin I.N.Z.; Gunasagaran V. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
Landslides susceptibility assessment has been conducted to identify the landslide-prone areas by using Geographical Information System (GIS) through Analytical Hierarchy Process (AHP) technique. Ten predictive or causative factors, such as digital elevation map (DEM), aspect, slope, curvature, geology, land use, fault, river, road and rainfall are used to map the susceptibility of landslides. Five classification zones of landslide susceptibility area are classes to very high, high, moderate, low and very low zone. The classification zones were compared and validated using a landslide inventory map produce from the integration of historical data and field survey using area under curve (AUC) method. The AHP technique final result shows 78.0% accuracy of landslide prediction, which considered as a fair result and it is acceptable. The mitigation measures for planning safe urbanization can be formulated using this susceptibility map. BEIESP.